Measuring Health Outcomes in HIV: Time to Bring in the Patient Experience. Issue 1 (5th January 2021) - O'Brien, Niki; Chi, Y-Ling; Krause, Karolin R.
Introduction: Over the past decade, the global response to HIV has led to a reduction in the number of new infections, and a decrease in associated mortality. Yet, the number of people living with HIV (PLHIV) is high, with an estimated 38 million infected worldwide. As HIV shifts from being an acute terminal illness to a chronic condition, evaluating programmatic responses to HIV with sole reliance on biological markers (such as viral load or CD4 cell count) as proxies for patient health may no longer be suitable. HIV affects the lives of those infected in myriad ways which should be reflected in programme evaluations by measuring health-related quality of life, in addition to biomarkers. Discussion: In this commentary we argue that there is a pressing need to review how a "good" health outcome is defined and measured in light of care systems moving towards value-based frameworks that measure value in terms of the actual health outcomes achieved (rather than processes of care), global response shifting to providing long-term care for PLHIV in the community, and integrating HIV as part of universal health coverage plans. Efforts should be directed towards validating generic and disease specific patient-reported measures of PLHIV, to identify the most suitable tools. Such efforts will ensure that patient experience is appropriately captured, especially to be used in programme or economic evaluations. Conclusions: It is only by recognising and measuring the full range of health, mental and social outcomes related to the disease that the health status of PLHIV can be fully understood.